Analysis Of Shell Structures In Nature - Mohamad Said, Mohd Nor Shahril (Universiti Sains Malaysia, 2005)
During the pass few decades, the development of shell structure in nature as a structural form has added an exciting chapter to contemporary architecture. As shells are form-active structure, proper choice of shape is very important in order to achieve high level of structural efficiency. With the development of computer technology and much computer software, computer stimulation has reached a high level of standard. The analysis of shell can be performed by using the finite element method. In this research, an investigation on the surface efficiency of selected seashell has been done. The data of seashell surface can be obtained by using “fringe projection” method. Static analysis under self-weight has been done with using different surface thicknesses. The model of the selected seashell can be generated by using finite element software ADINA. Since it is found that no research has been carried out in an attempt to investigate the structural efficiency of the seashell surface, this present research has been carried out with the objective to compare the structural advantages in term of strength and rigidity of the selected seashell. Through the analysis of the results, the distribution of bending moments, membrane forces, shear forces and vertical displacement can be examined. It has been found that the strength and rigidity of shell in the shape of seashell is quite good and acceptable as long as suitable material is used.